"Distribution, effective demand and international economic relations" - "Kregel, J.A. (ed.)" (London, 1983)
This volume represent the outcome of the first year of activity of the Centro di Studi Economici Avanzati, Trieste. The primary activity of the centre is the organistaion of a summer economics study programme which in 1981 brought more than 40 economists from 15 countries together in Trieste. The papers published here were first dscussed informally among participants in advance of their formal presentation during an open comfrence held at the beginning of September iin villa Manin di Passarino, Udine.
Keywords: Value distribution theory